Broadening the perspective of traditional lecturing vs. active learning in introductory college biology - Adam A. Aguiar; Jennifer Calabrese (Discover Education)
Abstract This research aimed to examine the effectiveness of traditional lectures versus active lectures in introductory college biology classes composed of science and non-science majors, a topic of significant importance in the field of education. In a traditional lecture, the researcher used PowerPoint to present class content while answering direct student questions. In contrast, an active lecture included a PowerPoint, a collaborative group activity, and class dialogue. Students were given pre- and post-class surveys to assess content learning and open-ended questions to examine learning preferences. The results demonstrate a significant increase in student understanding after both lectures, with a statistically more significant score change from the pre- to post-test for the active lecture. Moreover, students expressed a higher level of enjoyment in the active class. These findings underscore the potential of active learning in enhancing student understanding and engagement. Given the variability in learning approaches, this study highlights the importance of devising mechanisms to gauge and implement the optimal extent and types of active learning strategies. The study’s results suggested that reframing the active vs. traditional lecturing binary paradigm into a continuum may help instructors plan courses to best meet students’ needs.